2012
DOI: 10.1287/trsc.1110.0383
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Space and Time Partitioning for Yard Crane Workload Management in Container Terminals

Abstract: W e propose a new hierarchical scheme for yard crane (YC) workload management in container terminals.We also propose a time partitioning algorithm and a space partitioning algorithm for deploying YCs to handle changing job arrival patterns in a row of yard blocks. The main differences between our approach and most of the methods in literature are (1) the average vehicle job waiting time instead of the number of jobs is used to balance YC workload and to evaluate the quality of a partition, (2) the YC working z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…They then focused on the single yard crane dispatching and proposed two heuristic algorithms to minimize the average vehicle delay at the yard. A further study by Guo and Huang (2012) focused on the level 2 decision making, and proposed a time partition algorithm and a space partition algorithm to arrange the yard crane workload in a single row of yard blocks. Gharehgozli et al (2014) adopted a continuous time integer programming model to tackle the single yard crane scheduling problem with both storage and retrieval jobs in a single container block.…”
Section: Related Workmentioning
confidence: 99%
“…They then focused on the single yard crane dispatching and proposed two heuristic algorithms to minimize the average vehicle delay at the yard. A further study by Guo and Huang (2012) focused on the level 2 decision making, and proposed a time partition algorithm and a space partition algorithm to arrange the yard crane workload in a single row of yard blocks. Gharehgozli et al (2014) adopted a continuous time integer programming model to tackle the single yard crane scheduling problem with both storage and retrieval jobs in a single container block.…”
Section: Related Workmentioning
confidence: 99%
“…The second most important functionality is the "optimization of the space" of the yard. Several studies can be found in the literature showing the effect of optimization of the space in the yard [64][65][66][67][68]. The utilization of the yard in an optimal way can increase, for example, the efficiency of the equipment used in the yard by travelling shorter distances or reducing the number of moves needed to store a container in the storage yard.…”
Section: Discussionmentioning
confidence: 99%
“…A new approach that addresses these issues has been proposed in [12][13][14][15]. We are working to complete that work and will compare the performance with the YC deployment approach in this paper.…”
Section: Conclusion and Discussionmentioning
confidence: 99%